Meneropong makna kebijaksanaan dalam pemahaman teologi dan spiritualitas Kristen: Implikasinya terhadap pengambilan kebijakan pastoral - Angelus. H Tamonob; Louisa D. F. Bnani; Pedro A. P. Babys; Kanisius M. Tampani (STIPAS Keuskupan Agung Kupang, 2025)
The word wisdom is a complex word. It is said so because the word has both profane and sacred dimensions. Based on that, wisdom also has various contexts. Therefore, this article aims to explore the meaning of wisdom in a Christian perspective through a critical review of the Holy Scriptures (Biblical Theology), Christian Tradition, and spirituality. Additionally, this article also aims to examine the urgency of wisdom in the Christian perspective in the context of pastoral life based on pastoral facts. This article uses qualitative research methods. The data presentation technique employs a descriptive-analytical approach. The research found that, in the Old Testament, wisdom is centered on God (theocentric). In the New Testament, wisdom is centered on Christ (Christocentric). And in the tradition of the early church community, wisdom is Christocentric-Ecclesiocentric. Wisdom is then developed through spiritual movements and becomes part of virtuous actions or deeds. Ultimately, wisdom is greatly needed in the pastoral context.